Tendências nas horas dedicadas ao trabalho e lazer: Uma análise da alocaç\~ao do tempo no Brasil - Ana Luiza Neves de Holanda Barbosa (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– In this study we document trends in the allocation of time by gender in Brazil. In particular, we analyze trends in market work hours, home work hours (household chores), commute and leisure times in Brazil along 2001-2015. Analysis is made by gender and is based on the National Household Survey (PNAD). Results show that men enjoy more time of leisure than women, although this difference is reducing over time. For both men and women, there is an increase in leisure time. Specifically, we show that leisure for men increased by 4 hours per week (driven by a decline in market work hours) and for women by 7 hours per week (driven by a decline in home production work hours).
Keywords: D12; D13; J22; 330; time use; leisure; labor supply; gender